Interpretasi Gramatis Dan Psikologis Pada Cerpen Kafanu Al - Ustazi Karya Haifa Bitar : Analisis Hermeneutika Romantik Schleiermacher - Nizar, Mohammad; Faiz, Fahruddin (Philosophiamundi, 2023)
This research seeks to reveal the meaning of the short story "Kafanu Al - Ust??i" in the short story anthology Gur?bunwa Kit?bah by Haif?? B???r. The theory used to reveal meaning in research is Schleiermacher's romantic hermeneutics. The method used is a qualitative method with two typical Schleiermacher text interpretation models, namely Grammatical Interpretation and Psychological Interpretation. Grammatical interpretation aims to reveal the meanings of the short story "Kafanu Al - Ust??i" through word-to-word relationships (language analysis), while the meaning of grammatical interpretation will be completed through its relationship with the author based on Psychological Interpretation. Based on the analysis carried out on the short story "Kafanu Al - Ust??i" in the short story anthology Gur?bunwa Kit?bah by Haif?? B???r with Schleiermacher's romantic hermeneutic theory, several things were found: 1) women are human beings who must be considered equal to men, 2) the obstruction of women in achieving Her ideals are very likely caused by repression that comes from men, and 3) discrimination against women is something that cannot be justified.